Pengaruh air perasan curcuma longa terhadap penurunan lama nyeri pada penderita dispepsia - Clarissa, Elga Manda; Andora, Novika; Andini, Sandra (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Dyspepsia is a complex gastrointestinal symptom that is often encountered in daily clinical practice. This condition is characterized by a series of symptoms related to the gastroduodenal digestive tract, such as pain or a burning sensation in the upper abdomen (epigastrium). Purpose: To determine the effect of Curcuma longa juice on reducing the duration of pain in dyspepsia sufferers. Methods: Quantitative research with observational pre-experimental design and cross-sectional approach. The population in this study were dyspepsia sufferers who accidentally met the researcher and met the inclusion and exclusion criteria. The sample in this study amounted to 38 participans with the sampling technique used was Acidental sampling. Data analysis used univariate and bivariate analysis using the Wilcoxon Signed Rank Test and a confidence level of <0.05. Results: Wilcoxon test with statistical test with mean duration of dyspeptic pain before intervention was 11 but after intervention the average became 95 with p value of 0.000 <0.05 meaning there was an effect of squeezing cucuma longa on reducing duration of pain. Conclusion: Based on the results of the Wilcoxon Signed Rank Test, there is an effect of curcuma longa juice on reducing the duration of pain with a p-value of 0.000.   Keywords: Curcuma Longa; Dyspepsia; Pain.   Pendahuluan: Dispepsia merupakan gejala gastrointestinal (gastrointestinal symptoms) yang kompleks dan sering dijumpai dalam praktik klinis sehari-hari. Kondisi ini ditandai dengan rangkaian gejala yang terkait dengan saluran pencernaan gastroduodenal, seperti nyeri atau sensasi terbakar di daerah perut atas (epigastrium). Tujuan: Untuk mengetahui pengaruh air perasan curcuma longa terhadap penurunan lama nyeri pada penderita dispepsia. Metode: Penelitian kuantitatif dengan rancangan pra eksperimen observasional dan pendekatan cross-sectional. Populasi dalam penelitian ini adalah penderita  dispepsia yang tidak sengaja bertemu dengan peneliti dan sesuai dengan kriteria inklusi ekslusi. Sampel dalam penelitian ini berjumlah 38 partisipan dengan teknik sampling yang di gunakan adalah Acidental sampling. Analisis data menggunakan analisi univariat dan bivariat dengan menggunakan uji Wilcoxon Signed Rank Test dan derajat kepercayaan <0.05. Hasil: Pengujian wilcoxon menggunakan test statistic dengan mean lama nyeri dispepsia sebelum intervensi sebesar 11, setelah intervensi rata-rata menjadi 95 dengan nilai p sebesar 0.000<0.05 artinya ada pengaruh dari perasan cucuma longa terhadap penurunan lama nyeri. Simpulan: Berdasarkan hasil uji Wilcoxon Signed Rank Tes, terdapat pengaruh antara air perasan curcuma longa terhadap penurunan lama nyeri p-value 0.000.   Kata Kunci : Curcuma Longa; Dispepsia; Nyeri.